Vulnerability analysis of interdependent infrastructure systems: A methodological framework - Wang, Shuliang; Hong, Liu; Chen, Xueguang (Physica A, 2012)
Infrastructure systems such as power and water supplies make up the cornerstone of modern society which is essential for the functioning of a society and its economy. They become more and more interconnected and interdependent with the development of scientific technology and social economy. Risk and vulnerability analysis of interdependent infrastructures for security considerations has become an important subject, and some achievements have been made in this area. Since different infrastructure systems have different structural and functional properties, there is no universal all-encompassing ‘silver bullet solution’ to the problem of analyzing the vulnerability associated with interdependent infrastructure systems. So a framework of analysis is required. This paper takes the power and water systems of a major city in China as an example and develops a framework for the analysis of the vulnerability of interdependent infrastructure systems. Four interface design strategies based on distance, betweenness, degree, and clustering coefficient are constructed. Then two types of vulnerability (long-term vulnerability and focused vulnerability) are illustrated and analyzed. Finally, a method for ranking critical components in interdependent infrastructures is given for protection purposes. It is concluded that the framework proposed here is useful for vulnerability analysis of interdependent systems and it will be helpful for the system owners to make better decisions on infrastructure design and protection. ► A framework for interdependent infrastructure systems vulnerability analysis is proposed. ► Three types of attack strategy are proposed in this paper. ► Different interface topology design strategies are illustrated to minimize cascading failures. ► Both long-term and focused vulnerability analyses are studied in this paper.